Don’t Hurt Anybody, or You’ll Get the Mare: Connections between Common Cold and the Mythical Being slogutis in Lithuanian Folklore - Skujytė-Razmienė, Asta (Tautosakos darbai, 2017)
In the Lithuanian folk medicine, classification of illnesses rests on several aspects, including separation of sicknesses affecting children and grownups, or discerning conditions caused by other untreated troubles (like fright). Based on the level of contagiousness, infectious and noncommunicable illnesses are discerned. Those considered infectious encompass a rather broad range: from epidemic (like plague and cholera) to skin complaints (warts and scabies). The article is centered on the Lithuanian folk belief (LTR 1415/119/) attributing common cold to the infectious illnesses. Since this is an unprecedented case, the research aims at finding out if common cold was considered an infectious decease in the Lithuanian folk medicine and if so, on what grounds. The author attempts establishing a potential connection between cold (Lith. sloga) and the mythical being incubus (Lith. slogutis); also her aim is finding out if common cold meant the same thing in the 19th – 20th centuries as it does in the 21st one. According to the data from the “Dictionary of the Lithuanian Language”, other vernacular names for the cold (viral rhinitis) are established. This prompts deeper investigation of other possible meanings of the word sloga, thus leading to further examination of its fourth meaning – namely, the mythical being slogutis. According to etiological and folk belief legends, slogutis (incubus, or nightmare), a being that tortures people in their sleep, most frequently evolves from the dead unbaptized children. This being can appear both in anthropomorphic (child, man, woman, Jew) or zoomorphic (cat, dog, hen, pig) shape. Although in terms of gender slogutis correlates with the general European notion of succubus / incubus, it does not quite correspond to it. Motivation for choosing the victim could include disregard for the rules of the community life or violation of taboos, or perpetrating some wrongs (with slogutis as a punishment). There are references to oppression by slogutis as a form of revenge. Of course, in some cases the reasons for this torture remain unclear. Surveying of folklore and international contexts elucidates the notion of slogutis as a being threatening human health and life. Further analysis reveals that experiencing such nightmares was diagnosed as a decease, therefore slogutis could have been perceived not only as a supernatural being, but also as a sickness. The last part of the article deals with the notion of cold against the background of folk medicine. Apparently, some ways of treatment imply the notion of cold as something alien: there are attempts at creating a cold-unfriendly environment and mocking at the cold in hope it would feel offended and leave the patient alone. Sometimes people resorted to active measures and employed the pars pro toto principle attempting to destruct the sickness or to pass it onto somebody else. The research revealed that the notion of cold (rhinitis) is in some cases supplemented with elements of slogutis. This enables deeper understanding of the connection between those two sicknesses. Both synonymous usage (confusion) of the names and means of treatment allow asserting that cold and incubus (sloga and slogutis) could have been perceived as two sides of the same trouble – the external and the internal one. Although the data to prove the systematic status of cold / slogutis as an infectious decease in the folk medicine is scarce, the hypothetic possibility remains, encouraging further investigation of these materials.